Lay Counselor Perspectives of Providing a Child-Focused Mental Health Intervention for Children: Task-Shifting in the Education and Health Sectors in Kenya - Dorsey, Shannon; Meza, Rosemary D.; Martin, Prerna; Gray, Christine L.; Triplett, Noah S.; Soi, Caroline; Woodard, Grace S.; Lucid, Leah; Amanya, Cyrilla; Wasonga, Augustine; Whetten, Kathryn (Frontiers in Psychiatry, 2019)
The global mental health treatment gap has increasingly been addressed using task-shifting; however, very little research has focused on lay counselors’ perspectives on the acceptability, feasibility, and appropriateness of mental health interventions in specific government-supported sectors that might scale up and sustain mental health care for children and adolescents. In western Kenya, these sectors include Education and Health. Data come from a large hybrid effectiveness-implementation study examining implementation practices and policies in either or both sectors that support successful implementation of a child-focused intervention, Trauma-focused Cognitive Behavioral Therapy (TF-CBT), for children and adolescents who had experienced parental death. We examined lay counselors’ self-report of acceptability, feasibility, and appropriateness of TF-CBT. Lay counselors were teachers (n = 30) from the Education sector and Community Health Volunteers (CHV; n = 30) from the Health sector, who were part of Sequence 1 of this large stepped-wedge, cluster randomized trial. Lay counselor self-report surveys included reflective and formative measurement of acceptability, feasibility, and appropriateness administered after lay counselors in both sectors had experience delivering the locally-adapted, group-based TF-CBT intervention. Descriptive statistics (means, standard deviations) were used to understand counselors’ perspectives on reflective and formative measures, stratified by sector. Both teachers and CHVs endorsed high acceptability, feasibility, and appropriateness of TF-CBT, with lay counselors’ responses on items from the formative measures providing some insight into specific aspects of acceptability, feasibility, and appropriateness that may be important to consider when planning for implementation support. These early findings suggest that both sectors may hold promise for task-shifting of mental health care for children and adolescents but also underline the importance of considering the multiple facets of these three implementation outcomes as well as lay counselor context (Education vs. Health ).